RAGE and HMGB1 Expression in Orbital Tissue Microenvironment in Graves’ Ophthalmopathy - Dominika Łacheta; Krzysztof B. Poślednik; Katarzyna Czerwaty; Nils Ludwig; Marta Molińska-Glura; Ireneusz Kantor; Anna Jabłońska-Pawlak; Piotr Miśkiewicz; Alicja Głuszko; Zygmunt Stopa; Jacek Brzost; Mirosław J. Szczepański (Mediators of Inflammation, 2021)
Graves’ ophthalmopathy (GO) is a chronic autoimmune inflammatory disorder involving orbital tissues. A receptor for advanced glycation end products (RAGE) and its ligand high mobility group box 1 (HMGB1) protein trigger inflammation and cell proliferation and are involved in the pathogenesis of various chronic inflammatory diseases. This study was aimed to evaluate RAGE and HMGB1 expression in GO to determine its potential clinical significance. To the best of our knowledge, this is the first study showing RAGE and HMGB1 expression in orbital tissue using immunohistochemistry. Sections of orbital adipose tissue obtained from patients diagnosed with GO (23 patients; 36 orbits) and normal controls (NC) (15 patients; 15 orbits) were analyzed by immunohistochemistry for RAGE and HMGB1 expression. Expression profiles were then correlated with clinical data of the study group. RAGE and HMGB1 expression were elevated in GO patients in comparison with NC (p=0.001 and p=0.02, respectively). We observed a correlation between RAGE expression and occurrence of dysthyroid optic neuropathy (DON) (p=0.05) and levels of TSH Receptor Antibodies (TRAb) (p=0.01). Overexpression of RAGE and HMGB1 might be associated with GO pathogenesis. In addition, RAGE and HMGB1 proteins may be considered as promising therapeutic targets, but this requires further research.